2018
DOI: 10.1093/geronb/gby056
|View full text |Cite
|
Sign up to set email alerts
|

Variety of Enriching Early-Life Activities Linked to Late-Life Cognitive Functioning in Urban Community-Dwelling African Americans

Abstract: Results provide promising evidence that enriching early environments are associated with late-life educational and cognitive outcomes. Findings support the cognitive reserve and engagement frameworks, and have implications to extend life-span prevention approaches when tackling age-related cognitive declines, diseases, and health disparities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 57 publications
4
26
0
Order By: Relevance
“…281–290; James et al, 2012 ). Emerging research on childhood social activities also corroborate our results ( Chan et al, 2019 ).…”
Section: Conclusion and Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…281–290; James et al, 2012 ). Emerging research on childhood social activities also corroborate our results ( Chan et al, 2019 ).…”
Section: Conclusion and Discussionsupporting
confidence: 91%
“…Relative to the self-reported status collected in CHARLS, the housing characteristics (i.e., architecture type) has the advantage of objectivity and accuracy, which has been increasingly used in recent studies and recognized as a good indicator of individuals' SES ( Ghawi et al, 2015 ; Juhn et al, 2011 ). Secondly, neighborhood safety and neighborhood cohesion are used to measure the childhood neighborhood social environments, which could also be important for individuals’ long-term cognitive development ( Chan et al, 2019 ; Crosnoe, 2000 ; Wu et al, 2015 ; Yen et al, 2009 ). Third, childhood social relationships are captured by two measures: childhood friendship, childhood relationships with parents.…”
Section: Data Sets and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is initial evidence from a prospective study that traces of childhood SES are still present in the brain structure of young adults aged 23-25 years, even when adulthood SES is controlled for 189 . We do not yet know whether this is also true of older adults, but studies suggest that cognitive enrichment might be important: cognitive stimulation in childhood is associated with larger brain volumes 190 and better cognition in old age 191 when adulthood SES is controlled for. Furthermore, a longitudinal study showed that higher levels of early cognitive stimulation are associated with slower cognitive decline and less neuropathology with ageing 192 .…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…As suggested by prior literature, these four domains of childhood factors may influence cognitive aging through multiple pathways. For example, childhood SES (Kaplan et al, 2001;Marden et al, 2017), neighborhood social environment (Wu et al, 2015), social relationships (Chan et al, 2019;Crosnoe, 2000) and health conditions (Kobayashi et al, 2017;Nguyen et al, 2008;Zhang et al, 2010) have profound effects on early-life brain development, which contribute to the initial cognitive reserve and vulnerability to brain pathologies. The four childhood circumstances may also determine the completion of formal education, social status, and health or health behaviors in adulthood (Borenstein and Mortimer, 2016a;Chetty et al, 2016;Fletcher et al, 2020;Glewwe and Miguel, 2007;Luo and Waite, 2005), which in turn shape varying patterns of cognitive aging.…”
Section: Introductionmentioning
confidence: 99%